2018
DOI: 10.1159/000486018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Heterogeneity in Familial IgA Nephropathy

Abstract: Background: IgA nephropathy is the most common primary glomerulonephritis worldwide and a significant cause of end-stage renal disease (ESRD). While most cases of IgA nephropathy are considered sporadic, familial cases have been reported. Methods: We performed a national audit of 1,809 patients attending renal clinics and dialysis units to identify a family history among patients with kidney disease. We reviewed all renal biopsies performed at our institution spanning a 30-year period. Paediatric cases were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The incidence of family clustering is almost comparable to that in previous studies: 6.7% in China [ 8 ] and 17.2–34% in Italy [ 5 ] (Additional file 2 ). Other studies with Caucasians showed a lower frequency of familial aggregation in total sporadic cases: 1.8% in Ireland [ 6 ] and 1.4% in the US [ 15 ]. The difference in frequency of familial clustering may be due to the geographic and/or racial difference in genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of family clustering is almost comparable to that in previous studies: 6.7% in China [ 8 ] and 17.2–34% in Italy [ 5 ] (Additional file 2 ). Other studies with Caucasians showed a lower frequency of familial aggregation in total sporadic cases: 1.8% in Ireland [ 6 ] and 1.4% in the US [ 15 ]. The difference in frequency of familial clustering may be due to the geographic and/or racial difference in genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Families presenting with IgAN were identified through a clinical analysis carried out by Fennelly et al (15). Patients were selected on the basis that they had a clinical picture compatible with IgAN predominantly.…”
Section: Selection Of Familiesmentioning
confidence: 99%
“…DNA from these patients was obtained at Beaumont Hospital from these collected blood or saliva samples and processed through the Rare Kidney Disease Biobank at St. James Hospital, Dublin, Ireland. We then chose families who had at least one family member with biopsy proven IgAN and one other family member with either biopsy-proven IgAN or ESRD as previously described (15) and selected families that had at least two affected members with DNA available. This left us with ten families for the exome sequencing analysis.…”
Section: Selection Of Familiesmentioning
confidence: 99%
“…IgAN may occur in a sporadic or familial form[ 13 ]. Intriguingly, clinical manifestations of IgAN can overlap considerably with AS, which results from mutations in the COL4A3 , COL4A4 , and COL4A5 genes[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%